Access to Papanicolaou Test by the Unified Health System users - Vanessa Franco de Carvalho; Nalú Pereira da Costa Kerber; Vanessa Andréia Wachholz; Flávia Conceição Pohlmann; Letícia Amico Marques; Fabiane Ferreira Francioni (Rev Rene)
Objective: to understand how is the access to the public health service users in the Papanicolaou Test. Methods: qualitative study, with 52 women who have changes in the Pap smear exam, questioning the exam achievement frequency and the difficulties of its access and the consultations. It was developed a thematic analysis based on the Fekete accessibility reference.Results: three categories emerged: access to information on the frequency of Pap smears, highlighting the completion of the examination linked only to the professional application; access to Pap smears, in which most women do not have difficulty; access to a return visit, showing the difficulty of women getting back into service after the exam. Conclusion: most women have easy access to the Pap smear. However, there are limitations on the return visit, hindering to establish immediate actions to the beginning of treatment.